2017
DOI: 10.4172/2329-891x.1000247
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge about Antibiotic Use and Resistance among Students of Northern Border University Saudi Arabia

Abstract: Background: Irrational antibiotic use has led society to antibiotic resistance a serious health problem worldwide, which is now trying to be solved by many various approaches. In 2011, the World Health Day theme was "Combat drug resistance: no action today means no cure tomorrow".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our findings showed that most of the students were familiar with the term antibiotic resistance (85%). In comparison with the findings in KSA [23], results were similar and comparable (65%) but higher in UK [24]. This research, 4 th year students had the highest percentage which shows that their knowledge and practice helped them to be more familiar.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our findings showed that most of the students were familiar with the term antibiotic resistance (85%). In comparison with the findings in KSA [23], results were similar and comparable (65%) but higher in UK [24]. This research, 4 th year students had the highest percentage which shows that their knowledge and practice helped them to be more familiar.…”
Section: Discussionsupporting
confidence: 59%
“…This common problem usually happen as they might believe, that antibiotics will relief their illness faster. Amoxicillin/Clavulanate was the most common drug used by the students which was also reported in KSA 68% [23], and reported in community settings in Yemen (52.35%) [28], and Indonesia (46%) [29]. The reason for it's highly usage is due to its effect on respiratory tract infections and it's commonly prescribed by physician.…”
Section: Discussionmentioning
confidence: 78%
“…Globally irrational antibiotic use has led society to antibiotic resistance which is a serious health problem [12] .…”
Section: Introductionmentioning
confidence: 99%